PENDEKATAN MODEL ASUHAN KEPERAWATAN HOLISTIK SEBAGAI UPAYA PENINGKATAN KEPUASAN DAN KESELAMATAN PASIEN DI RUMAH SAKIT - MUNDAKIR, MUNDAKIR (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: to develop Holistic Nursing Care Model as effort to enhance patients’ satisfaction and safety in Hospital. Methods: Exploratory Mixed-Method with R & D cycle approach was used. There were 3 steps in this study which are pre-development step, development step, and step of implementation model. Nurses in in-patient ward Siti Khodijah Sepanjang Hospital were become a sample in this study. Total sampling technique was performance. The independence variable was nursing care holistic model and the dependent variables were patients’ satisfaction and safety. Survey, observation, focus group discussion, and questionnaire were used as data collection technique. Thematic analysis was used to analyzed the qualitative data and descriptive analysis was used to analyzed the quantitative data. Results: Patients’ satisfaction and safety were the problems in nursing care in Siti Khodijah Sepanjang Hospital. The implementation of nursing care in Siti Khodijah Sepanjang Hospital was nearly to nursing care holistic model. This study established the conceptual of nursing care holistic model to enhance patients’ satisfaction and safety. Conclusion: The implementation of nursing care holistic model is nurse’s responsibility in provide comprehensive nursing care to solve patient’s problems. The implementation of nursing care holistic model is patient oriented technique. This order has done to retrieval patient problems and provided the right solutions.